Molecular Characterization Of 17 Accessions Of Gymnema Sylvestre R. Br. Using Rapd Markers - R. BALAMURALI KRISHNA; SUJITHA R. REDDY REDDY; M. VIJAYALAXMI; K.ANUGNA; N. DIVYAVANI; K. JAGADEESWARA REDDY (International Journal of Pharma and Bio Sciences, 2012)
Gymnema sylvestre is a large, stout, woody, vine-like plant which climbs on bushes and trees. It is known in Sanskrit- Meshashiringi, Madhu nashinin (Madhu=sugar, nashini= destroy), in Hindi- Gur-mar. The Latin name of Gymnema Sylvestre means “sugar destroyer” and is considered as herbal remedy for high blood sugar. It is considered to be a very effective antidiabetic plant in Indian indigenous system of medicine. In view of its importance and the genetic diversity of this species in India, we attempted to characterize 17 accessions of Gymnema sylvestre using Random Amplified Polymorphic DNA (RAPD). Out of 20 primers tested from OPL group, four were selected, which gave 48 clear and bright fragments, out of which 24 (50%) fragments were considered as polymorphic. The amplicons usually ranged from 500bp to 2500bp. The Dendrograms generated by UPGMA analysis were compared based on the gymnemic acid content. The major cluster I comprised 4 accessions from Warangal-I, with high gymnemic acid content (42%), Warangal-II (38.6%), Mulugu-I (40.4%) and OU-Botanical garden (31.4%). The major cluster II had two accessions from OU-Hyderabad with lower gymnemic acid content 23% and 26.6%. The major cluster III had minor clusters with 11 accessions. One cluster with samples 2, 13, 3, 14, 10, 11 and 12 had higher gymnemic acid content ranging from 32 to 39%. The results of the present study clearly suggested that anti-diabetic Gymnema sylvestre can be characterized through RAPD markers and high value superior accessions can be identified for product development in control of diabetes.